1994
DOI: 10.1098/rspa.1994.0137
|View full text |Cite
|
Sign up to set email alerts
|

Influence of solute additions on the fracture behaviour of Armco iron

Abstract: The influence of solutes, namely cobalt, molybdenum, nickel and silicon, on the deformation and fracture behaviour of Armco iron has been studied. The J -integral method was used for the measurement of ductile initiation fracture toughness J IC . Although cobalt is seen to enhance significantly J IC of the starting material (Armco iron), molybdenum, nickel and silicon are observed to have a deleterious effect. The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…In a recent study on the influence of solute addition on the fracture behavior of Armco iron, NiSiCr and NiSiCrCo alloys, the increase in fracture toughness with cobalt addition was attributed to grain boundary segregation of carbon. 64 which increased the intergranular cohesive strength and rendered the crack initiation process difficult. 64 It was observed that in the presence of cobalt there was displacement of sulfur from the grain boundaries by carbon through a site-competitive process.…”
Section: Relevance Of Intergranular Segregation Processes In the Undementioning
confidence: 99%
See 2 more Smart Citations
“…In a recent study on the influence of solute addition on the fracture behavior of Armco iron, NiSiCr and NiSiCrCo alloys, the increase in fracture toughness with cobalt addition was attributed to grain boundary segregation of carbon. 64 which increased the intergranular cohesive strength and rendered the crack initiation process difficult. 64 It was observed that in the presence of cobalt there was displacement of sulfur from the grain boundaries by carbon through a site-competitive process.…”
Section: Relevance Of Intergranular Segregation Processes In the Undementioning
confidence: 99%
“…64 which increased the intergranular cohesive strength and rendered the crack initiation process difficult. 64 It was observed that in the presence of cobalt there was displacement of sulfur from the grain boundaries by carbon through a site-competitive process. The increase in the intergranular cohesive strength by carbon segregation was substantiated through yield stress dependence on grain size that the Hall-Petch constants 0 and k y were influenced.…”
Section: Relevance Of Intergranular Segregation Processes In the Undementioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is advisable not to use Co MPs in the formation of the Fe + 0.5 % C alloy as it may reduce the strength of the material. Srinivas et al found that the addition of 0.5 wt.% Co MPs led to changes in the structure and lowered the yield strength of Armco iron by about 70 MPa [21].…”
Section: Microstructural and Mechanical Properties Of Fe+05 % C Alloy With Modifiersmentioning
confidence: 99%
“…• Srinivas, Malakondaiah, and Rama Rao found that Fe-Co alloys (0.5 wt.% and 5 wt.% Co) resulted in lower yield strength but no effect on the tensile strength compared to the base material unalloyed ARMCO Iron. In contrast to molybdenum, nickel, and silicon, cobalt significantly increased the fracture toughness (JIC) [54].…”
Section: Cobaltmentioning
confidence: 93%